Delay control in multi-class multi-server RST-based communication networks via M/K setting - Babiker, Amin; Mohammed Ahmed Mahmoud, Muawia; El-Azhary, Ismail; Mohd. Ramli, Huda Adibah (IJCSNS, 2013)
In this paper, analysis of non-preemptive priority queues with multiple servers and multiple priority classes, which is based on Residual Service Time (RST) is utilized to calculate the total waiting time for system customers. Definitely, this waiting time is determined by several parameters such as the number of servers, the order of the priority class to which the customer belongs and the total number of customers in the system. Analysis results show that the same waiting time can be attained by different Priority class order/ Number of Servers combinations. Accordingly, these parameters could be used in determining the desired level of performance expressed in terms of waiting time. The obtained results of waiting times and their relations with priority class orders and Number of Servers could help a lot in justifying and supporting this proposed RST-Based Analysis